Design of a machine - Retractable emergency bridge - Augusto Emilio Caceres Nuñez (2024)
In this project we analyzed how to apply engineering to some useful place especially within our country, Peru; that is why the idea of using a mobile retractable bridge for emergencies arose, we noticed that every year there are strong landslides especially in Lima, and to date there is no concrete proposal to safeguard the lives of people living in risk area, only prevention activity is done but not something concrete. The use of the mobile retractable bridge will be done through the use of contactors logic, which will allow the deployment and contraction of a bridge through the control of an electric motor; where this bridge will be designed for easy transport to different places.